Statin therapy correlated CYP2D6 gene polymorphism and hyperlipidemia. (February 2014) - Li, Juyi; Wang, Xiufang; Zhang, Zhaoqing; Zou, Jili; Chen, Yonggang; Wang, Xiong; Wu, Jinhu
Abstract Purpose: To investigate the distribution of statin therapy correlated gene polymorphism allele CYP2D6*10 (C188T) in Ningxia Hui nationality and to discuss the relationship between the gene polymorphism allele CYP2D6*10 (C188T) and the lipid-lowering efficacy of simvastatin and hyperlipidemia. Materials and methods: One hundred and fifty healthy people (80 males and 70 females) and 200 hyperlipidemia patients (105 males and 95 females) were recruited at Ningxia People's Hospital. Genotypes were determined by using allele-specific amplification (ASA-PCR) in 150 healthy controls and 200 patients with hyperlipidemia. Relationships between genotypes and lipid levels and the lipid-lowering efficacy of simvastatin were analyzed. Results: The distribution frequency of the CYP2D6*10 allele was 47.6% in the Ningxia Hui nationality. There was no significant correlation between the CYP2D6*10 allele and hyperlipidemia. At 8 weeks after treatment with simvastatin, total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels were more obviously decreased with the CC genotype than the CT and TT genotypes, with significant differences. Conclusion: Distribution of the gene polymorphism of CYP2D6*10 is ethnically and geographical different. The allele T of CYP2D6*10 is not related to hyperlipidemia. CC expression seemed to increase the lipid-lowering effects of simvastatin. The hyperlipidemia patients with CC genotype should take lower doses of simvastatin than those with CT/TT genotype in the Ningxia Hui population.